Anti-Tumor Necrosis Factor Alpha-Associated Multiple Sclerosis - Titelbaum, David S. (AJNR Am J Neuroradiol, 2005)
Summary: A case of multiple sclerosis presenting during anti–tumor necrosis factor treatment for rheumatoid arthritis is discussed. This association has been reported in the nonradiological literature, but is an important association for radiologists to be aware of, as they may be in a position to first suggest the diagnosis.